2003
DOI: 10.7186/bgsm46200351
|View full text |Cite
|
Sign up to set email alerts
|

The kinematics of deformation of the Kenerong Leucogranite and its enclaves at Renyok waterfall, Jeli, Kelantan

Abstract: The Late Cretaceous Kenerong Leucogranite, a component of the Stong Complex exposed near TNB mini power station, at Renyok waterfall, Jeli, Kelantan consists of a sequence of leucogranite vein and metasedimentary enclaves. Here, varieties of structures developed in both rock types. Structural studies indicate the rocks here had undergone at least four phase of defonnation. It is interpreted that the first defonnation (D 1) with the compression from ESE, which was responsible in the development of foliation and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 1 publication
1
5
0
Order By: Relevance
“…3). Previous studies have shown that this meta-sedimentary sequence is diverse and can be described as meta-clastic with some intercalations of meta-carbonate and amphibolite (Hutchison, 2009;Abdullah and Setiawan, 2003;Singh et al, 1984). It contains hornblende-quartz schists, staurolite-garnet biotite schists, tourmaline bearing mica schists, diopside-phlogopite marbles, sillimanite-garnet-biotite gneiss and amphibolite.…”
Section: The Stong Complex and Taku Schistmentioning
confidence: 98%
See 3 more Smart Citations
“…3). Previous studies have shown that this meta-sedimentary sequence is diverse and can be described as meta-clastic with some intercalations of meta-carbonate and amphibolite (Hutchison, 2009;Abdullah and Setiawan, 2003;Singh et al, 1984). It contains hornblende-quartz schists, staurolite-garnet biotite schists, tourmaline bearing mica schists, diopside-phlogopite marbles, sillimanite-garnet-biotite gneiss and amphibolite.…”
Section: The Stong Complex and Taku Schistmentioning
confidence: 98%
“…Four phases of deformation have been proposed through field observations at the classical Renyok waterfall outcrop, which exposes the Kenerong granite and its high-temperature metamorphosed host rock sequence (6i,j in Fig. 3, Abdullah and Setiawan, 2003). Late Cretaceous foliation, isoclinal folding and veining took place during the emplacement of the intrusion and was followed by two phases of NW-SE contraction associated with boudinage, kink, ptygmatic and drag-folding, and (later) normal faulting.…”
Section: The Stong Complex and Taku Schistmentioning
confidence: 99%
See 2 more Smart Citations
“…Renyok waterfall consists of a sequence of sub-parallel stretched leucogranite veins and metasedimentary enclaves. Ibrahim Abdullah and Jatmika Setiawan (2003) concluded that the rocks had undergone at least four phases of deformation.…”
Section: Granitoidsmentioning
confidence: 99%